IDENTIFIKASI KESULITAN BELAJAR MATERI STRUKTUR FUNGSI JARINGAN TUMBUHAN PADA SISWA KELAS X SMA - Laia, Yetti Mani Dewi Sartika (TUNAS : Jurnal Pendidikan Biologi, 2024)
This study aims to identify the Learning Difficulties of Students in the Material of Plant Tissue Structure and Function in Grade X Students at SMA Negeri 1 Amandaraya for the 2022/2023 Academic Year. The approach used in this research is qualitative, employing a descriptive research type that describes, analyzes, and interprets existing data. Qualitative research is a method aimed at gaining an understanding of reality through an inductive thinking process. The results obtained during the research activities include: (1) suboptimal intelligence among students, (2) attitudes toward learning, (3) learning motivation, (4) concentration in learning, and (5) study habits. The conclusion of this research indicates that students experience several difficulties in participating in classroom learning activities, influenced by both internal and external factors. Internal factors include fatigue, health/stability, and psychological factors such as interest, talent, motivation, and concentration. External factors encompass family influences, including parenting styles, family relationships, home environment, school factors such as teaching methods/teacher relationships, and societal factors including mass media and peer interactions. The researcher recommends that: (1) to succeed in learning and avoid difficulties, students should enhance their motivation, concentration, response, understanding of the material, and strive for maximum grades. Students should also choose beneficial activities to engage in at home for study purposes, (2) teachers should optimize the potential of both struggling and non-struggling students by incorporating more engaging teaching media and activities, and (3) parents should be more assertive in guiding their children at home to ensure they study regularly and engage in more beneficial activities.